Determinants of exchange rate: a case study of Malaysia / Zulkifli Mohd Nasir and Mohamed Nazim Khairi Mohamed Khir - Mohd Nasir, Zulkifli; Mohamed Khir, Mohamed Nazim Khairi (Faculty of Business and Management, 2016)
The aim of this study is to investigate factors affecting exchange rate in Southeast Asian countries which is focusing on Malaysia. The dependent variable of this study is exchange rate while independent variables are price of oil, growth domestic product (GDP), inflation rate and interest rate. The data collected covers the period from 1997 until 2015. This study employs time series in order to study the relationship between those variables. The result of this study found that inflation rate and interest rate has positive significant relationship with exchange rate. We are focusing on the fluctuation price of oil will give the impact the volatility of exchange rate. The main objective is to investigate whether there is a relationship between selected independent variables and exchange rate in Malaysia. The methodology use in this research is secondary data that collected from data stream. We analyse the raw data using Econometric-view 9 (EView9). Our finding prove that the independent variable price of oil and gross domestic product GDP) are significant with dependent variable exchange rate. For the other researcher, they should focus or highlight on relationship between price of oil and gross domestic product (GDP) towards exchange rate.